MAPPING OF AREAS OF FOREST AND LAND FIRE VULNERABILITY IN THE SANIANG BAKAR AREA, X KOTO DISTRICT, SOLOK DISTRICT - rezki, sri; Edial, Helfia; Iswandi, Iswandi; Triyatno, Triyatno (Remote Sensing Technology Study Program, 2024)
This research uses quantitative descriptive analysis which has the title